Surgical versus medical intervention for the treatment of concurrent otitis media with effusion in children undergoing adenotonsillectomy in the age group 5-15 years: a prospective comparative study - Pulimoottil, Davis T.; Karthikeyan, Padmanabhan; Venkataramanujam, Nirmal C.; Kaipuzha, Ramiya R.; Philip, Angel Cham (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The aim was to study the prevalence of otitis media with effusion (OME) among children with concurrent chronic adenotonsillitis or adenoid hypertrophy and to study the outcomes of various modalities of treatment. Methods: Over 2 years, 100 children in the age group 5-15 years undergoing adenotonsillectomy were included of which, patients diagnosed with concurrent OME were sequentially allocated into 2 groups. Group I was adenotonsillectomy and medical therapy and group II was adenotonsillectomy and myringotomy with grommet insertion. Results: The prevalence of OME among children in the age group 5-15 years undergoing adenotonsillectomy is 21%. There is a statistically significant relationship between male gender, middle socioeconomic status, joint families, history of bottle feeding, history of exposure to parental smoking and prevalence of OME. Group II fared better in terms of clinical outcomes following surgical intervention, with a success rate of 100%. Conclusions: Surgical treatment for OME has a better clinical outcome as compared to just medical therapy for the same.